Intention to join a union in peruvian professional workers: analysis of determining factors - Yong Chung, Felipe Eduardo; Fuchs Angeles, Rosa María; Jauregui Arroyo, Ralphi Ricardo; Bonilla Bermeo, Jeniffer Denisse (Revista Venezolana de Gerencia, 2026)
In a context where higher education coverage is expanding across Ibero-America, a greater proportion of professionally trained workers is projected. Hence, the aim of this study is to identify the main factors influencing the union affiliation intention among Peruvian professional workers. To this end, a cross-sectional, non-experimental research design was applied, involving a sample of 639 respondents. The collected data were analyzed using structural equation modeling via partial least squares (PLS). The study demonstrates that the primary determinant of union affiliation intention is the workers’ beliefs—whether accurate or not—about the unions’ benefits in terms of labor protection, followed by occupational stress and work-life balance. Furthermore, the results indicate that the main determinant of the psychological capital of Peruvian professional workers is their work-life balance.